Study the Effectiveness of Massive Transfusion Protocol at Srinagarind Hospital Faculty of Medicine, Khon Kaen University - Chau-In, Waraporn; Soontrapa, Sukree; Puapairoj, Jintana; Sirijerachai, Chittima; Rangsrikajee, Dhaness; Thanapaisal, Chaiyut; Chongsomchai, Chompilas; Romphruk, Amonrat; Theechaatik, Panor; Puttamas, Auayporn; Chanawongse, Rachanee; Riratapong, Saowaluck; et al. (ศรีนครินทร์เวชสาร, 2013)
Background and Objectives: The major policy for patient safety in a tertiary care hospital includes practice guidelines or support system for hemorrhagic crisis, and the establishment of the expert working team. Multidisciplinary group of Srinagarind Hospital, Faculty of Medicine, compose of the anesthesiologist, surgeon, obstetrician, hematologist, team personnel from operating room, delivery room, accidental – emergency unit, laboratory unit and central blood bank. Working team jointly establishes guidelines for the management of massive blood transfusion protocol (MTP) and applied it to context of each department. Working team monitors and audits the MTP approach by comparing the results of the project in the year 2010 and 2011. Methods: We performed a retrospective study to evaluate the performance of the work instruction of massive transfusion protocol. Outcome measurements were result in a rapid blood usage within recommendation time, costs for blood and blood components and survival rate within 7 days as indicators of the MTP project. Results: There were 22 cases of patients of surgery, who used the MTP, 14 patients of surgical ward, 5 patients of orthopedic ward, two cases of delivery room and one from medical ward. The average time for a request - receive blood from the blood bank established in 2010 and 2011 were 22.50 + 2.89 and 18.33 + 7.64 minutes respectively. The difference time was no statistically significant (p=0.352). A cost arising from the use of the 182 units of blood during surgery in the study year was 76,743 Baht. The survival rates within 7 days after surgery were 57 and 61.5 percent, respectively. Conclusion: The massive transfusion protocol decrease duration time of blood arrival to operating room and increase survival rate within 7 days, if all relevant guidelines were followed step by step. Keywords: massive transfusion protocol, patients’ outcome